Glucagon‐like peptide‐1 in the rat brain: Distribution of expression and functional implication. Issue 10 (19th April 2013) - Gu, Guibao; Roland, Barbara; Tomaselli, Kevin; Dolman, Carrie S.; Lowe, Carolyn; Heilig, Joseph S.
Abstract Glucagon‐like‐peptide 1 (GLP‐1) is expressed not only in gut endocrine cells, but also in cells in the caudal brainstem and taste buds. To better understand the functions of central GLP‐1, GLP‐1 expression was immunohistochemically profiled in normal rat brain and its distribution correlated with FOS induction following systemic administration of a GLP‐1 receptor agonist, exendin‐4. In the present study, only a small number of GLP‐1‐immunoreactive cell bodies were observed in the nucleus of the solitary tract (NTS). However, these neurons send abundant projections to other regions of the brain, in particular the forebrain, including the paraventricular and dorsomedial nuclei of the hypothalamus, the central nucleus of the amygdala, the oval nucleus of the bed nuclei of the stria terminalis, and the paraventricular nucleus of the thalamus. Intraperitoneal administration of exendin‐4 resulted in extensive FOS expression in areas of the forebrain and the hindbrain. In the forebrain, FOS expression was largely confined to regions where a high density of GLP‐1‐immunoreactive terminals was also localized. The majority of GLP‐1‐immunoreactive cells in the NTS were not FOS‐positive. FOS‐positive cells appeared to represent a different population from those expressing GLP‐1. Thus, GLP‐1‐containing neurons in the brainstem may not be involved in receiving and relaying to other regions of the brain the physiological signals of prandial GLP‐1 secreted by intestinal L‐cells. Projections of GLP‐1‐containing neurons to the distinctive structures in the forebrain imply that central GLP‐1 may play an important role in the behavioral and metabolic integration of autonomic control and arousal in the rat. J. Comp. Neurol. 521:2235–2261, 2013. © 2012 Wiley Periodicals, Inc.